La franchise : un contrat sui generis dangereux - Gagnon, Jean H. (Assurances, 1989)
During the past decade, the growth of franchising, a business phenomenon, has, from all standpoints, been astounding. Franchising law, however, is still at its beginnings, at least in Quebec. This law is not independent of other laws since its elements are drawn here and there from other sectors of business law. Our collaborator, Me Jean H. Gagnon, primarily examines two aspects of franchising : the contract and the inherent risks of franchising. This article should prove useful to readers interested in this concept as there are no laws which apply specifically to franchising and since the future of this area of activity is very promising.